Lateral deformation and defect resistance of compacted silica glass: Quantification of the scratching hardness of brittle glasses - Sawamura, Shigeki; Limbach, Rene; Behrens, Harald; Wondraczek, Lothar (Journal of Non-Crystalline Solids, 2018)
Human interaction with multimedia devices occurs predominantly over inorganic glass surfaces. Scratch-induced damage is a primary limitation in the suitability of brittle glasses for this purpose. However, neither truly quantitative data nor a topo-chemical understanding of the underlying deformation process which would allow for the development of improved materials is presently available. Here, we present lateral nano-indentation experiments for determining the work of deformation which is involved in the process of glass scratching. Using a series of hot-compressed vitreous silica with mild degrees of structural densification, we derive relations between quantitative scratch hardness and the underlying glass structure. We show that Young's modulus provides a clear rational for the observed variations in scratching hardness. In the specific case of silica, the energy needed to generate a certain scratch volume corresponds to roughly one tenth of Young's modulus. This relationship formally indicates that only about one tenth of the bonds which are involved in the deformation process are broken in its course. However, comparison with a more complex glass material with a certain fraction of two dimensional structural units and a strong ability for topological adaption to local stress clearly indicates a deviation from this behavior. This opens a pathway to topo-chemical engineering of scratch-resistant glasses.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Glass; Scratch hardness; Scratch resistance; Silica